Pengetahuan dan Sikap Wanita Premenopause dalam Menghadapi Perubahan-Perubahan pada Masa Menopause - Ria Afriani; Tina Yuli Fatmawati (Universitas Baiturrahim, 2020)
Elderly women are found around 8-10% in the State of Indonesia whose health must get the attention of the community so that happiness and well-being are achieved. A woman at a certain age will experience climacteria where there is a natural change in her body. Changes that occur during menopause consist of short-term effects such as physical changes in skin changes, under-skin fat is reduced so that the skin becomes saggy, skin is flammable to the sun and cause pigmentation and blackening, muscles under the skin of the face relax and fall and become soft, this condition can cause discomfort in everyday life. Knowledge of menopause will help climacteric women to be able to prepare themselves and be able to act and act appropriately in preventing the occurrence of disturbances that occur accompanying menopause. This research is a descriptive study to find out the description of knowledge and attitudes of premenopausal women in dealing with changes during menopause. The population in this study were all pre-elderly women at the Kenali Besar Health Center in Jambi City. The samples taken by accidental sampling technique amounted to 44 people. This research was conducted in 2019 at the Kenali Besar Health Center in Jambi City. Data collection through interviews using a questionnaire. Data were analyzed univariately. The results were obtained from 44 respondents, 17 respondents (39%) had good knowledge, 11 respondents (25%) had enough knowledge and 16 respondents (36%) had poor knowledge. The results of attitudes obtained most of the respondents have a negative attitude that is 22 respondents (55%), positive attitudes as many as 20 respondents (45%). Most respondents have good knowledge and negative attitudes